Calmodulin and calcium-dependent protease I coordinately regulate the interaction of fodrin with actin. - Harris, A S (1990)
The calcium-dependent proteolysis of fodrin has been implicated in the regulation of secretion, neutrophil and platelet activation, and long-term potentiation in neurons. In vitro studies indicate that calcium-dependent protease I (calpain I) cleaves fodrin in the middle of the alpha subunit and in the COOH-terminal third of the beta subunit. Cleavage at the beta site requires calmodulin, which binds with high affinity to a single site in the alpha subunit. In vitro binding assays, nondenaturing gel electrophoresis, and velocity sedimentation identify a linkage between calcium-dependent protease I proteolysis of fodrin and the ability of calmodulin to regulate the self-association of fodrin and its interaction with actin. Three functional states appear to exist: (i) intact fodrin, which constitutively forms tetramers and binds F-actin; (ii) alpha-cleaved fodrin, which loses its ability to self-associate and bind F-actin in the presence of calmodulin; and (iii) alpha,beta-cleaved fodrin, a form that is incompetent to establish tetramers or bind actin. Because actin binding and fodrin self-association occur at opposite ends of the molecule, whereas calmodulin binds at its center, these results indicate that long-range interactions exist within fodrin. They also offer an example of how two calcium-dependent regulatory processes may act synergistically to reversibly regulate a linkage between the membrane and the cytoskeleton.